G. I. Martynova: NOMINATION OF PHYSICAL AND PHYSIOLOGICAL CONDITIONS OF HUMAN BEINGS IN MIDDLE-UPPER-DNIEPER DIALECTS - Мартинова, Ганна Іванівна; Scherbyna Т. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Introduction.The anthropocentric orientation of modern scientific research encourages the study of language in close connection with the spiritual and practical activities of man, his consciousness, thinking, which is manifested in the specifics of nominating of the environment, selection of methods and means of nominating realities. Dialectal speech needs special attention, because, on the one hand, the nomination in dialects occurs casually and naturally, and on the other hand changes in the socio-economic and cultural life of dialect speakers, one of the consequences of which are active dynamic processes in vocabulary. phenomena that over time become inevitably lost. The article continues a series of publications by the authors about the name of a person in the Middle -upper-Dnieper dialects. Purpose. The aim of our research is to study the means of verbalization and methods of nomination of elements of the thematic group “Man”, in particular the names of physiological states of man in the Middle-upper-Dnieper dialects. Results. The names of physical and physiological states of man in the middle -upper-Dnieper dialects are different in structure, belonging to lexical and grammatical classes, the presence or absence of emotionally expressive coloring. Some of these nominations are neutral, many names are emotionally expressive. The main function of connotative names is to qualify, evaluate, characterize the physical and physiological state of a person from the position of the speaker. The factual material shows that among the expressive names there are many individual word-formations, they are mostly subjective, arise in a specific speech and relate to the characteristics of specific persons. The structural core of the studied nominations is formed by one-word names – adjectives, nouns; attributive phrases are less often attested. The least frequent are propositional and discursive names. A productive way of nomination in the studied area is suffixation, semantic derivation. The most common motive for the nomination of the analyzed names is the resemblance to domestic animals and household items. There are tokens of darkened motivation. Originality. The names of physical and physiological states of man in the dialects of the Middle Dnieper region have not yet been the object of study, so the representation of their repertoire, structure and semantics of names, the study of the features of the nomination is the novelty of this article. Conclusions. In the “Dictionary of Middle-upper-Dnieper dialects” in the illustrative mini-texts to the dictionary articles the diversity of material and spiritual life of dialect bearers is reflected. The names of physical and physiological states of the person are widely presented in it. It is possible to find out the nuances of meaning, the motives of nomination of tokens attested in different zones of the Middle-upper-Dnieper dialect only in reliance on the context, on the explanation of the informant himself.